2005
DOI: 10.1103/physrevlett.95.066402
|View full text |Cite
|
Sign up to set email alerts
|

Mott Transition and Kondo Screening inf-Electron Metals

Abstract: We study how a finite hybridization between a narrow correlated band and a wide conduction band affects the Mott transition. At zero temperature, the hybridization is found to be a relevant perturbation, so that the Mott transition is suppressed by Kondo screening. In contrast, a first-order transition remains at finite temperature, separating a local-moment phase and a Kondo-screened phase. The first-order transition line terminates in two critical end points. Implications for experiments on f-electron materi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
220
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(249 citation statements)
references
References 25 publications
29
220
0
Order By: Relevance
“…Meanwhile, Koga et al found an OSMT using exact diagonalization (ED), applied to the full J-model, 13 but not for the J z -model. 14 Consequently, the OSMT scenario was attributed to spin-flip and pairhopping processes.Very recently, four preprints appeared, 15,16,17,18 in which the OSMT was investigated in detail within the DMFT framework. Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Koga et al found an OSMT using exact diagonalization (ED), applied to the full J-model, 13 but not for the J z -model. 14 Consequently, the OSMT scenario was attributed to spin-flip and pairhopping processes.Very recently, four preprints appeared, 15,16,17,18 in which the OSMT was investigated in detail within the DMFT framework. Ref.…”
mentioning
confidence: 99%
“…Very recently, four preprints appeared, 15,16,17,18 in which the OSMT was investigated in detail within the DMFT framework. Ref.…”
mentioning
confidence: 99%
“…Above 0.8 GPa at 298 K, pure Ce metal undergoes an isostructural transition from an a face-centered cubic (fcc) phase (␥-Ce) to a denser, high-pressure, fcc phase (␣-Ce) accompanied by a 15% volume collapse. Since its discovery by P. W. Bridgman in 1927 (10), the ␥-␣ Ce transition has been the subject of extensive experimental (11,12) and theoretical investigations (7,(13)(14)(15)(16) and is often cited as an archetypal example of a localizeditinerant 4f electronic transition. Various scenarios including Mott transition (7), Kondo hybridization (8,13), and intermediate behaviors between the two (14, 15) have been proposed.…”
mentioning
confidence: 99%
“…(1) What is the role of the spin-orbit interaction (SOC) for the volume-collapse? (2) What is the fate of the pressure-temperature transition-line at very low temperatures [16][17][18]? (3) Can a first-principle based theory be made computationally efficient so as to access both the γ and the α Cerium at zero temperature?…”
mentioning
confidence: 99%